2021
DOI: 10.2967/jnumed.120.258574
|View full text |Cite
|
Sign up to set email alerts
|

Matched-Pair Comparison of 18F-DCFPyL PET/CT and 18F-PSMA-1007 PET/CT in 240 Prostate Cancer Patients: Interreader Agreement and Lesion Detection Rate of Suspected Lesions

Abstract: IntroductionTens of different Prostate Specific Membrane Antigen (PSMA) targeting radiopharmaceuticals for both imaging and therapy have been synthesized. Although variability in biodistribution and affinity for binding to the PSMA receptor between different PSMA targeting radiopharmaceuticals are known, little is known about the clinical implications of those variabilities. Therefore, in this study differences in interreader agreement and detection rate between two regularly used 18 F-labeled PSMA-receptor ta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
38
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(41 citation statements)
references
References 25 publications
3
38
0
Order By: Relevance
“…However this information may still play an important role in pre-operative surgical planning, choice of treatment modality (radiotherapy may be preferred over exenterative surgery for T4 disease), guiding the extent of radiotherapy treatment (extension of local tumour volume delineation to cover adjacent in ltrated bladder, rectum and/or elective treatment of pelvic lymph nodes (21,22), and the use of androgen deprivation therapy (23). These imaging ndings are consistent with most literature, including a matched pair comparison of 240 scans with [ 18 F]PSMA-1007 vs F-DCFPyl identi ed suspected prostate/prostatic fossa lesions in a higher proportion of [ 18 F]PSMA-1007 scans, particularly for the indication of biochemical recurrence (24). Also in the setting of biochemical recurrence, [ 18 F]PSMA-1007 has previously been shown to be at least as accurate as [ 68 Ga]Ga-PSMA-11 (14,15,25).…”
Section: Discussionsupporting
confidence: 81%
“…However this information may still play an important role in pre-operative surgical planning, choice of treatment modality (radiotherapy may be preferred over exenterative surgery for T4 disease), guiding the extent of radiotherapy treatment (extension of local tumour volume delineation to cover adjacent in ltrated bladder, rectum and/or elective treatment of pelvic lymph nodes (21,22), and the use of androgen deprivation therapy (23). These imaging ndings are consistent with most literature, including a matched pair comparison of 240 scans with [ 18 F]PSMA-1007 vs F-DCFPyl identi ed suspected prostate/prostatic fossa lesions in a higher proportion of [ 18 F]PSMA-1007 scans, particularly for the indication of biochemical recurrence (24). Also in the setting of biochemical recurrence, [ 18 F]PSMA-1007 has previously been shown to be at least as accurate as [ 68 Ga]Ga-PSMA-11 (14,15,25).…”
Section: Discussionsupporting
confidence: 81%
“…In this regard, some new PSMA molecules labeled with other radioisotopes, such as 18 F, were developed [ 107 ]. Fluoride-18 is a cyclotron-generating radioisotope that has more favorable characteristics than 68 Ga, including production in larger quantities, transportation to satellite centers, longer physical half-life, delayed imaging, theoretically better spatial resolution [ 108 , 109 , 110 ], and possibly detection of smaller lesions due to lower positron energy [ 107 , 111 ]. Also, [ 18 F]PSMA-1007 has biliary excretion.…”
Section: Targeting Agentsmentioning
confidence: 99%
“…Except for [ 18 F]PSMA-1007, there are other clinically available 18 F-labeled PSMA agents ([ 18 F]DCFPyL and [ 18 F]DCFBC) [ 113 , 114 , 115 , 116 ]. Despite some differences, which may influence our preference for clinical use, all seem equally effective for imaging of PCa [ 111 , 112 , 117 ]. Very recently, [ 18 F]FDCFPyL was also approved by FDA for staging and re-staging of PCa.…”
Section: Targeting Agentsmentioning
confidence: 99%
See 1 more Smart Citation
“…Among them, 68 Ga-PSMA-11 and 18 F-DCFPyL have been consecutively approved by the FDA for patients with primary and recurrent PCa ( 9 , 10 ). Nevertheless, although 18 F-based tracers offer important advantages such as higher production capacity, longer physical half-life, and minimal radiotracer accumulation in the bladder ( 11 – 13 ); up until now, 68 Ga-PSMA-11 is still worldwide the most commonly used and provides the absolute majority of evidence in the literature for PSMA imaging. Importantly, many accuracy studies and two previous meta-analyses have reported favorable diagnostic performance of 68 Ga-PSMA-11 PET/CT for the detection of pelvic lymph node metastases (PLNMs) in intermediate to high-risk PCa ( 14 – 17 ).…”
Section: Introductionmentioning
confidence: 99%